2022
DOI: 10.3389/fendo.2022.877010
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between FT3 With the Outcome and Inflammation/Coagulopathy/Fibrinolysis of COVID-19

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic has caused substantial threats to people’s physical health and lives, claiming the lives of over 5 million people worldwide. It is imperative to identify the disease severity and intervene with effective therapy as early as possible. Previous studies have shown that low free triiodothyronine (FT3) may possess the predictive value on COVID-19 prognosis.MethodsIn this retrospective cohort study, 15-day clinical and laboratory data of 186 hospitalized pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In addition, we observed relatively higher levels of ALB and HDL, along with lower levels of TBil and LDL in patients infected with the Delta variant compared to those infected with the original SARS-CoV-2. Our previous research has shown that low HDL level and high TBil level may be correlated with a poor prognosis in patients with original COVID-19 ( 25 , 26 ). Given the large-scale vaccination program that was already underway in China When the Delta variant emerged in 2021, the above changes of hematological parameters may be explained by the protective effect of vaccines ( 27 ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, we observed relatively higher levels of ALB and HDL, along with lower levels of TBil and LDL in patients infected with the Delta variant compared to those infected with the original SARS-CoV-2. Our previous research has shown that low HDL level and high TBil level may be correlated with a poor prognosis in patients with original COVID-19 ( 25 , 26 ). Given the large-scale vaccination program that was already underway in China When the Delta variant emerged in 2021, the above changes of hematological parameters may be explained by the protective effect of vaccines ( 27 ).…”
Section: Discussionmentioning
confidence: 97%
“…As with most other diseases, low T3 syndrome occurs in patients with COVID-19. This was first described in patients admitted to hospital with COVID-19 in Wuhan (China) in 2020, who were found to have serum T3 concentrations lower than normal, the extent of decline proportional to severity of disease, and independently associated with mortality [2][3][4]. A systematic review subsequently identified 163 studies of thyroid hormone and COVID, with seven specifically reporting the association in ICU patients.…”
Section: Coronavirus Disease 2019mentioning
confidence: 99%
“…The high prevalence of coagulopathy in patients infected with the coronavirus 2019 (COVID-19) pandemic and its well-documented association with the substantial elevation in mortality rates and unmet clinical outcomes have prompted many researchers to investigate coagulopathy-relevant abnormalities, such as elevated D-dimer levels, fibrin degradation product, and prolonged prothrombin time in this patient population. [1–4] Complete autopsies of deceased COVID-19 patients, including postmortem computed tomography, supported by a plethora of studies in critically ill patients, have identified deep venous thrombosis and subsequent pulmonary embolism as hallmarks of pandemic-related deaths. [5–7] Furthermore, patients with COVID-19 frequently have pulmonary and extrapulmonary microthrombotic and thromboembolic indicators as well as significant pulmonary angiogenesis.…”
Section: Introductionmentioning
confidence: 99%